VIRTUAL TANGRAM AS A TOOL FOR TEACHING GEOMETRY: AN EXPERIENCE REPORT IN ELEMENTARY EDUCATION - Rosa Nogueira, Telmo (Journal of Interdisciplinary Debates, 2025)
This experience report presents the use of the virtual Tangram, available on the Racha Cuca website, as a pedagogical tool for teaching geometry in elementary education. The study was conducted with 6th to 9th grade classes, including students with Autism Spectrum Disorder (ASD). The main objective was to evaluate the potential of the digital resource to promote engagement, inclusion, and consolidation of geometric concepts. The methodology included an initial demonstration, practical activity, and final discussion. The results showed a high level of student engagement, support for inclusion, and reinforcement of mathematical concepts, despite challenges related to fine motor skills. It is concluded that the virtual Tangram is an effective and accessible strategy to make the teaching of geometry more dynamic, playful, and inclusive.